2019
DOI: 10.1155/2019/2747205
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Vertical Vibration Mechanism of Reciprocating Compressors considering Flexibility of Piston Rod and Crosshead Subsidence

Abstract: This paper is targeted on the vertical vibration of the crosshead in a reciprocating compressor, taking into consideration the crosshead subsidence. The traditional model of the compressor is usually a crank-slider mechanism system without considering the abrasion loss for any parts, thus neglecting the influence of the piston rod flexibility. A rigid-flexible model of slider-crank is described theoretically, in which the crank, connecting rod, and crosshead are treated as rigid bodies, while the piston rod co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Through the dynamic analysis of the rigid and flexible model of the main moving mechanism of the reciprocating compressor, which regards the crank connecting rod as a rigid body and the piston rod as a flexible cantilever beam, it is found that the stiffness of the piston rod and the dynamic characteristics of the crankshaft change periodically with the change of cylinder pressure. [12][13][14] As the key component of the compressor, the dynamic characteristics of the crankshaft are bound to affect the movement of the piston rod and the dynamic behavior of the piston. Based on this consideration, some scholars established the rigid and flexible coupling dynamics model of the crankshaft system from the perspectives of crankshaft torsional vibration, modal analysis, and piston rod vibration using the multi-body dynamics theory and finite element method, and analyzed the vibration characteristics of the crankshaft, the modal change of the piston rod and the eccentric vibration of the piston under the action of load in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Through the dynamic analysis of the rigid and flexible model of the main moving mechanism of the reciprocating compressor, which regards the crank connecting rod as a rigid body and the piston rod as a flexible cantilever beam, it is found that the stiffness of the piston rod and the dynamic characteristics of the crankshaft change periodically with the change of cylinder pressure. [12][13][14] As the key component of the compressor, the dynamic characteristics of the crankshaft are bound to affect the movement of the piston rod and the dynamic behavior of the piston. Based on this consideration, some scholars established the rigid and flexible coupling dynamics model of the crankshaft system from the perspectives of crankshaft torsional vibration, modal analysis, and piston rod vibration using the multi-body dynamics theory and finite element method, and analyzed the vibration characteristics of the crankshaft, the modal change of the piston rod and the eccentric vibration of the piston under the action of load in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Model analysis and vibration analysis of the crankshaft and connecting rod mechanism inside the reciprocating compressor could predict the vibration of the piston rod but not the transverse oscillation motion. [23][24][25][26][27][28] So far, the transverse dynamic oscillation of the piston inside the labyrinth compressor are remained to reveal based on the real physical model of the piston, such as adopting the pressure load on the piston.…”
Section: Introductionmentioning
confidence: 99%